High blood pressure & pregnancy: an introduction - Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Jamani, Nurjasmine Aida (Malaysian Integrated Medical Professionals Association, 2022)
Hypertension is the leading chronic cardiovascular disease (CVD) affecting 5.8 million Malaysians. The prevalence of hypertensive disorders of pregnancy (HDP) in Malaysia is approximately 23.3 per 1000 live births. HDP can cause both maternal and foetal morbidity and mortality. It is also an independent risk factor of CVD with endothelial dysfunction postulated as the main pathophysiology.